The art and science of live, virtual, and constructive simulation for test and analysis. (April 2014) - Hodson, Douglas D.; Hill, Raymond R.
Live, virtual, and constructive (LVC) simulation technologies are well-established in the areas of technology demonstration, mission rehearsal, and exercises. A promising new role for LVC simulation technology is to facilitate weapon systems testing by producing defendable results. Requirements to test new defense systems within a system-of-systems context and within joint force scenarios have placed demands on physical test ranges that are not likely to be met. The LVC testing option promises the breadth and depth of defense systems, either as real or simulated assets, to potentially meet the new test demands. However, leveraging this technology to support testing will require a shift in the approaches used by the LVC community. In this paper, we discuss the challenges facing the LVC testing initiative, both from an experimental and from an architectural and implementation standpoint.